Convergence of a Conservative Difference Scheme for the Zakharov Equations in Two Dimensions (Journal of Computational Mathematics, 1997)
A conservative difference scheme is presented for the initial-boundary-value problem of a generalized Zakharov equations. On the basis of a prior estimates in $L_2$ norm, the convergence of the difference solution is proved in order $O(h^2+r^2)$. In the proof, a new skill is used to deal with the term of difference quotient $(e_{j,k}^n)t$. This is necessary, since there is no estimate of $E(x,y,t)$ in $L_∞$ norm.